IMPROVING THE SPEAKING SKILLS BY USING PICTURE SERIES - Siti Julaihah (Jurnal Penelitian)
Background of this study is an effort to know which technique is suitable to use in teaching speaking. Teaching a foreign language is considered to be one of the most challenging teaching practices. In Indonesia, students are usually afraid of joining foreign language classes. They may feel unmotivated and discouraged easily. Their mindsets say foreign language is difficult to learn because most of them know nothing from the start. Usually, students know nothing how to express what they want to say. Students who have learned English for several years have not been can communicate used English. So the researcher thought that there should be a solution to cope with that problem. The researcher tried to use describing picture as a method to improve students’ speaking skill especially in descriptive text